Enterotoxigenicity of Staphylococci isolated from dehydrated soup mixes - ΚΟΪΔΗΣ, Π.; ΜΑΝΤΗΣ, Α.; ΚΑΤΖΑΠΑΝΝΑΚΗΣ, Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
Staphylococcus aureus strains isolated from dehydrared soup mixtures were tested for their ability to produce entrotoxins. From a total of 153 tested, 37 (24.1%) were found to produce enterotoxin A. 143 (93.4%) were coagulase positive and 136 (88.7%) produced thermostable DNase. All enterotoxinogenic strains produced coagulase and thermostable DNase were isolated from 27 samples of the same origin. The strains tested were grown on Casein hydrolysate broth (BBL) and supernatant was concentrated to 1/50 of the original volume and tested with the microslide technique against A,B,C|, C,„D and E anti-enterotoxins.